ENHANCING STATISTICAL UNDERSTANDING THROUGH PjBL, VIRLENDA, AND WHATSAPP: A STUDY IN UNIVERSITAS PGRI ADI BUANA SURABAYA - Lydia Lia Prayitno; Ninik Mutianingsih (MATEMATIKA DAN PEMBELAJARAN, 2021)
This study was motivated by the difficulties of students transforming the data into frequency tables and graphs and appreciate a group of data. This is envolve in low student understanding. Encounter this situation, researchers felt the need to carry out CAR to rise these problems through PjBL supported by Virlenda and Whatsapp due to the pandemic situation that did not allow offline learning. So, the purpose of this study is to enhance students' statistical understanding through PjBL supported by Virlenda and Whatsapp. The subject 10 students from the 2019-C class of mathematics education program, Universitas PGRI Adi Buana Surabaya. Data were collected through observation, documentation, and tests. The data were analyzed quantitatively and qualitatively. The indicators of this study are there is no statistical understanding of students in the category less than "Good Enough" and observation components such as the focus of attention, activity, interest in learning, and seriousness of at least 70% of students. The results of this study, (1) the statistical understanding of all students in the minimum category of "Good" in the second cycle; (2) The observation component to the focus attention, activity, interest, and seriousness in learning satisfy criteria. This shows that the practice of PjBL supported by Virlenda and Whatsapp can improve the statistical understanding of students of mathematics education class 2019-C.